Polityka pieniężna a cykle koniunkturalne w strefie euro - Borowiec, Jan (Monetary Policy and Euro Area Business Cycles, 2009)
The aim of the article is to define the ECB role in stabilization of the euro area economy. While conducting its monetary policy, the ECB supported general economic policy in terms of economic activity stabilization. The ECB interest rates changed usually in alignment with the euro area business cycle fluctuations. The effectiveness of production fluctuations reduction depends not only on the interest rates movements. Changes in real effective exchange rates, on which the ECB has only a small influence, have weakened or enhanced its effects. Stabilization actions were also hampered by oil shocks. Wage rigidity in member countries became an obstacle in output stabilization by interest rates moves as well. Furthermore, ECB monetary policy was exposed to time inconsistency risk due to uncertainty of business cycle forecasting as well as the monetary policy transmission mechanisms. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 514-524